Topiramate Adjunctive Therapy for Olanzapine Induced Weight Gain in Patients with Schizophrenia - Pandit, Sanjib (Journal of Karnali Academy of Health Sciences, 2019)
In recent days, the prevailing use of second generation antipsychotics (SGA) or atypical antipsychotics over conventional antipsychotics have shifted the concern of physician from extra pyramidal side effects to the weight gain in the patients receiving treatment for schizophrenia. Among others atypical anti-psychotics, the phenomenology of Olanzapine related weight gain is highly recognized in the clinical practice. However, the exact mechanism by which Olanzapine exerts weight gain effect is largely not understood and is very likely to be multi-factorial. Among other several risk factors, factors such as 5HT2c polymorphisms and H1 receptor affinity have also been purposed. Similarly, various neuro-endocrinal factors related in maintaining energy homeostasis have also been observed to be affected by Olanzapine treatment. However no consisting findings are available to clearly explain the underlying psycho-pathology of disease spectrum in schizophrenia. However, though, recent finding from a clinical trial carried out in healthy male volunteers have suggested that the low baseline TSH profile predicts Olanzapine related weight gain and also interestingly relief by Topiramate adjuvant therapy. However, no such investigations were found in schizophrenia patient.